Investor-state dispute settlement (UN New YorkUS, 2014)
Focusses on the investor-State dispute settlement (ISDS) clause, or the ISDS chapter, regularly included in international investment agreements (IIAs). Aims at presenting a contribution to the debate (the pros and cons of the ISDS mechanism) by systematically analysing the components of ISDS.
Keywords: INTERNATIONAL INVESTMENT